Pengaruh Sistem Pengendalian Internal dan Moralitas Individu Terhadap Pencegahan Fraud Pengelolaan Keuangan Desa : Studi pada Dinas PMD Kabupaten Timor Tengah Selatan - Septianing K. Saununu; Anthon S. Y. Kerihi; Yohana F. Angi (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This research aims to find out the influence of the internal control system and individual morality on the prevention of fraud in the financial management of the village in South Central Timor District. The population in this study is the village chief, village secretary, village finance chief and village finance and wealth management department at the PMD department of South Central Timor District. This study employed a quantitative research methodology, which makes use of survey techniques. The scope of this research includes two independent variables, namely the internal control system and individual morality, and one dependent variable, namely fraud prevention. The data source used is the primary data source. The data collection is done by spreading the questionnaire. 69 questionnaires are distributed and 59 are processed. Data analysis techniques use descriptive statistical analysis, data quality tests, classical assumption tests, double linear regression analysis and hypothesis tests. The results of the research show that (1) the internal control system has a positive influence on the prevention of fraud in village financial management (2) the morality of individuals has a positive impact on fraud prevention in village finance management (3) the system of internal control and individual morality have simultaneously influenced on the preventing of frauds in village financing management.